Examining cultural drifts in artworks through history and development: cultural comparisons between Japanese and western landscape paintings and drawings - Nand, Kristina; Masuda, Takahiko; Senzaki, Sawa; Ishii, Keiko (Frontiers in Psychology, 2014)
Research on cultural products suggest that there are substantial cultural variations between East Asian and European landscape masterpieces and contemporary members’ landscape artwork (Masuda et al., 2008), and that these cultural differences in drawing styles emerge around the age of 8 (Senzaki et al., 2014). However, culture is not static. To explore the dynamics of historical and ontogenetic influence on artistic expressions, we examined (1) 17th to 20th century Japanese and Western landscape masterpieces, and (2) cross-sectional adolescent data in landscape artworks alongside previous findings of elementary school-aged children, and undergraduates. The results showed cultural variations in artworks and masterpieces as well as substantial “cultural drifts” (Herskovits, 1948) where at certain time periods in history and in development, people’s expressions deviated from culturally default patterns but occasionally returned to its previous state. The bidirectional influence of culture and implications for furthering the discipline of cultural psychology will be discussed.